Long-Term Survival of Patients With Advanced Heart Failure Receiving an Left Ventricular Assist Device Intended as a Bridge to Transplantation: The Registry to Evaluate the HeartWare Left Ventricular Assist System. (March 2020) - Zimpfer, Daniel; Fiane, Arnt E.; Larbalestier, Robert; Tsui, Steven; Jansz, Paul; Simon, Andre; Schueler, Stephan; Strueber, Martin; Schmitto, Jan D.
Abstract : Background: The paucity of available hearts for transplantation means that more patients remain on durable left ventricular support for longer periods of time. The Registry to Evaluate the HeartWare Left Ventricular Assist System was an investigator-initiated multicenter, prospective, single-arm database established to collect post-Conformité Européene mark clinical information on patients receiving the HeartWare ventricular assist device system as a bridge to transplantation. This registry represents the longest multicenter follow-up of primary left ventricular assist device outcomes. Methods: Data were collected on 254 commercial implants performed between February 2009 and March 2012 from 9 centers in Europe (7) and Australia (2). Patients were followed to device explant, heart transplantation, or death. The outcomes of patients through July/August 2018 were analyzed. Summary statistics were used to describe patient demographics, adverse events, length of support, and outcomes for this extended-term cohort. Results: A total of 122 patients were on support for >2 years, and 34 patients were on support for >5 years. Twenty nine patients are still alive on support (support ranging from 1213 to 3396 days), and 23 of those are on their original HeartWare ventricular assist device system. Kaplan–Meier survival through 7 years was 51%. Through 6 years, freedom from any stroke was 82%, while freedom from severely disabling stroke was 89%. Conclusions: Low rates of heart transplant now require longer periods of left ventricular assist device support in patients. This analysis demonstrates that long-term support using a HeartWare ventricular assist device system offers survival of 51% through 7 years.